The dispute over the origins of the Proto-Bulgarians and Gagauz - Klejn, Zbigniew (Balcanica Posnaniensia. Acta et studia, 2007)
The article addresses the issue of the origins of the Proto-Bulgarians and Gagauz people – a topic that has long been present in historiography and, after the end of the Cold War, has taken on new significance in Bulgarian scientific and political discourse. The background to the analysis is the fact that during the period of Soviet ideological domination, the role of the Proto-Bulgarians in the formation of the Bulgarian nation was marginalised, with emphasis placed on the Slavic element, which served to justify the policy of denationalising the Turkish minority. The collapse of the communist system allowed for a revision of these views and revived the debate in which researchers, often educated at Western universities, once again emphasise the importance of the Proto-Bulgarians. The aim of this article is to present the main lines of the debate on the ethnogenesis and language of the Proto-Bulgarians and their relations with other peoples of Eurasia, as well as to indicate the place of the Gagauz in this discussion. The paper draws on existing literature on the subject, archaeological research findings and linguistic data. The conclusions indicate that there is no clear answer as to the origin of the Proto-Bulgarians. Theories about their Turkic-Hunnic, Finno-Ugric, Iranian or even autochthonous origins compete with each other, with new archaeological discoveries and linguistic research undermining existing patterns. Similarly, the findings concerning the Gagauz are ambiguous.